"We All Believe in Breastfeeding": Australian Midwives' Experience of Implementing the Baby Friendly Hospital Initiative. (November 2022) - Pramono, Andini; Smith, Julie; Bourke, Siobhan; Desborough, Jane
Background: The education and support of new mothers during the in-hospital stay for childbirth is a critical time to establish breastfeeding. The Baby-Friendly Hospital Initiative was launched in 1991 to encourage maternity services to support and educate mothers to breastfeed by implementing Ten Steps to Successful Breastfeeding. Research Aim: To explore midwives' experiences of implementing the Baby-Friendly Hospital Initiative in a Baby-Friendly accredited public hospital in Australia. Methods: In this prospective, cross-sectional qualitative study we used focus groups to explore midwives' experiences. Midwives ( N = 26) participated in two focus groups conducted between October and November 2019. Data were analyzed using thematic analysis. Results: Time as a critical resource, and continuity of care, were crosscutting themes that framed midwives' experiences in supporting mothers to breastfeed their babies. Time constraints were experienced both through the health system structure and the BFHI accreditation process. Despite the challenges, the overarching theme—that we all believe in breastfeeding—fueled midwives' motivation. Conclusion: Health services policy and practice need to consider ways to enable continuity of midwifery care and adequate time for midwives to support women to breastfeed their babies.